Analysis of the Health of Sharia Cooperatives as an Effort for Creative Economy Development in Bojonegoro Regency, Indonesia - Nurul Mazidah; Dina Alafi Hidayatin (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Sharia-based cooperatives are financial institutions that use the principles of an Islamic economic system in running their business. As one of the economic actors, sharia cooperatives take part in the development of the creative economy in Indonesia. Improved management and good service can be done by applying the cooperative health calculation as a form of operational performance evaluation. This is also part of the cooperative development strategy. The purpose of this study was to determine the level of health of AKAS cooperatives. The calculation and analysis method is based on Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 07/Per/Dep.6/IV/2016. The results of the study concluded that the health of the AKAS cooperative was in a healthy condition from all aspects except the aspects of independence and growth.